Chemiluminescence analysis method based on carbon nitride quantum dots

Through the chemiluminescence analysis method based on carbon nitride quantum dots, the problems of high cost, high toxicity and poor selectivity of chemiluminescence reagents in the existing technology are solved, and efficient and sensitive detection of dopamine and iodine ions is achieved.

CN119354950APending Publication Date: 2025-01-24LONGYOU COUNTY INSPECTION & INSTITUTE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411506616.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The inorganic chemiluminescence reagents used in the existing chemiluminescence analysis methods are expensive, have high toxicity, poor analytical selectivity and low luminescence efficiency, and lack efficient new chemiluminescence systems.

Method used

The chemical luminous analysis method based on carbonate-based quantum dots (G-CNQDS) is used to prepare G-CNQDS through the green solid phase method, and coexist with K3 [Fe (CN) 6] to produce a strong chemical light response. In addition, the use of G-CNQDS as a receptor of chemical luminous resonance energy transfer to enhance the chemical light of the CE (IV) -so32-system.

Benefits of technology

It achieves an efficient chemiluminescence reaction, significantly improves the selectivity and sensitivity of analysis, has a good linear relationship and a low detection limit, and has potential application value for the detection of dopamine and iodide ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119354950A_ABST
    Figure CN119354950A_ABST
Patent Text Reader

Abstract

The invention discloses a chemiluminescence analysis method based on carbon nitride quantum dots, and relates to the technical field of chemiluminescence analys.The chemiluminescence analysis method comprises the steps that S1, the carbon nitride quantum dots are prepared through a green solid phase method and used for chemiluminescence detection of dopamine; s2, applying chemiluminescence resonance energy transfer of the carbon nitride quantum dots to iodide ion detection. According to the chemiluminescence analysis method based on the carbon nitride quantum dots, the chemiluminescence reaction mechanism of g-CNQDs-K3 [Fe (CN) 6] is researched by deeply researching an ultraviolet visible spectrum, a chemiluminescence spectrum, a fluorescence spectrum, electron paramagnetic resonance and an infrared spectrum, K3 [Fe (CN) 6] injects holes into the g-CNQDs, the holes can be compounded with thermally excited electron radiation of the g-CNQDs to generate chemiluminescence, and on the basis, the chemiluminescence analysis method has the advantages that the chemiluminescence reaction mechanism of the g-CNQDs-K3 [Fe (CN) 6] is researched; a g-CNQDs-K3 [Fe (CN) 6] chemiluminescence system is established, a flow injection chemiluminescence method is established to detect dopamine in serum, and an analysis result shows good selectivity and high sensitivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of chemiluminescence analysis, in particular to a chemiluminescence analysis method based on carbon nitride quantum dots. Background Art

[0002] Graphitic carbon nitride (g-C3N4) is a two-dimensional sheet material composed of tris-s-triazine as the parent structure and stacked in the form of graphite. As a typical semiconductor material with a medium valence band, it can catalyze a series of reactions in the visible light range, such as water decomposition, CO2 reduction, pollutant degradation, organic synthesis, and sterilization. In recent years, the optical properties of carbon nitride have also received widespread attention and have been used in the study of optical analysis methods. Due to the excellent fluorescence properties of carbon nitride, it has been successfully used in fluorescence sensing, long-life luminescence sensing, bioimaging, confidential inks, and chemiluminescence. Carbon nitride has great prospects in optical applications, and its luminescence properties and optical applications need to be further explored.

[0003] Chemiluminescence is a phenomenon in which two or more reactants undergo a redox reaction under appropriate reaction conditions to produce unstable excited intermediates or excited products, which return to the ground state and release energy in the form of light radiation, generating electromagnetic radiation. Chemiluminescence has attracted widespread attention from scientists due to its advantages of simple instrumentation, high detection sensitivity, wide analytical linear range, elimination of interference from background light scattering, and ease of automation, and has become an effective and rapid analytical method that has been successfully used in environmental monitoring, drug analysis, industrial analysis, biological immunity, and other fields.

[0004] In the past, inorganic chemiluminescent reagents used in chemiluminescent analysis included luminol and its derivatives, lucigenin, peroxy oxalate, potassium permanganate and tetravalent cerium. However, these traditional luminescent systems are usually expensive, highly toxic, have poor analytical selectivity and low luminescence efficiency. Seeking new chemiluminescent reagents, creating new chemiluminescent systems and improving chemiluminescence efficiency have become a major challenge in chemiluminescence research. At the same time, exploring the luminescence mechanism of these new chemiluminescent systems has also caused a research boom.

[0005] However, the rise of nanomaterials has injected new blood into chemiluminescence. The size and surface tunable properties of nanomaterials have improved the analytical effect of chemiluminescence. Among them, carbon nitride has excellent fluorescence properties, adjustable emission, easy functionalization, high quantum yield and biocompatibility. It can significantly improve the luminescence performance and improve the analytical effect when used in chemiluminescence.

[0006] In summary, carbon nitride has great application prospects in the field of chemiluminescence, and the exploration of luminescence mechanism and practical analytical application are the current research focuses of chemiluminescence analysis. The present invention studies and improves the existing technology and its shortcomings, and provides a chemiluminescence analysis method based on carbon nitride quantum dots. Summary of the invention

[0007] The object of the present invention is to provide a chemiluminescence analysis method based on carbon nitride quantum dots to solve the problems raised in the above background technology.

[0008] To achieve the above object, the present invention provides the following technical solution: a chemiluminescence analysis method based on carbon nitride quantum dots, comprising the following steps: S1. Green solid-phase method for preparing carbon nitride quantum dots for chemiluminescent detection of dopamine S11. Experimental reagents and instruments: prepare all reagents and instruments required for the experiment; S12, preparation of g-CNQDs: g-CNQDs with high fluorescence efficiency were prepared by thermal decomposition of melamine and EDTA; S13, g-CNQDs-K3[Fe(CN)6] chemiluminescence: The kinetic curve of g-CNQDs-K3[Fe(CN)6] chemiluminescence was obtained by static injection chemiluminescence, and the chemiluminescence image and intensity were obtained under the condition of negative high voltage -880V of photomultiplier tube with integration time of 0.1s; S14. Result analysis: K3[Fe(CN)6] is a commonly used chemiluminescent oxidant. In this study, it was found that K3[Fe(CN)6] and g-CNQDs would produce strong chemiluminescence when they coexisted. S2. Carbon nitride quantum dot chemiluminescence resonance energy transfer for iodide ion detection: S21. Experimental reagents and instruments: prepare all reagents and instruments required for the experiment; S22. Chemical treatment of g-CNQDs: 0.1 mol / L NaBH4 was added dropwise to g-CNQDs and stirred for 2 h at room temperature, then placed in an ultrasonicator (100 W) for 10 h, and dialyzed in ultrapure water for 2 days to remove excess reducing agent to obtain reduced rg-CNQDs; dialyzed g-CNQDs, Ce(IV) and SO3 2- The mixed solution after the reaction obtained oxidized og-CNQDs; the obtained rg-CNQDs and og-CNQDs solutions were freeze-dried, weighed, and dissolved in ultrapure water in the same mass and stored in a refrigerator at 4°C; S23, Ce(IV)-SO3 2- -g-CNQDs chemiluminescence process: Ce(IV)-SO3 2- --The kinetic curve of g-CNQDs chemiluminescence was based on static injection chemiluminescence; S24. Result analysis: Under the optimal experimental conditions, the analytical sensitivity of different concentrations of iodine ions was detected. The chemiluminescence signal and iodine ion concentration were (3.0×10-5 –3.0×10 -7 )mol / L has good linearity.

[0009] Furthermore, in step S11, the experimental reagents include a conductivity of 18.2 MΩcm -1 Deionized water, melamine, disodium ethylenediaminetetraacetic acid, dopamine, 0.1M phosphate buffer solution, Na2HPO4 and NaH2PO4, etc.

[0010] Furthermore, in step S11, the experimental instruments include a BPCL ultra-weak chemiluminescence analyzer, a transmission electron microscope (TEM), an atomic force microscope (AFM), an XSAM800 (Kratos) XPS, etc.; The transmission electron microscope (TEM) is to drop the sample aqueous solution on the copper mesh carbon film, dry it under an infrared lamp to be tested, and then place it in a Tecnai G2 F20 S-TWIN (FEI) field emission transmission electron microscope under an operating voltage of 200KV to characterize the material; The atomic force microscope (AFM) (Agilent 5500AFM) is used to drop the sample aqueous solution on the surface of the new mica sheet, dry it in vacuum at 60°C, and then scan and measure the sample thickness on the AFM using a cantilever probe tapping mode.

[0011] Furthermore, in step S12, the specific preparation steps of g-CNQDs are as follows: 0.126 g (1 mmol) of melamine and 0.248 g (0.67 mmol) of EDTA were mixed and ground into a uniform powder, and the obtained mixed powder was placed in an alumina crucible and placed in a muffle furnace and calcined at 350° C. for 1 hour; After cooling to room temperature, 30 mL of ultrapure water was added to obtain a brown solution, and the byproducts with larger particles were removed by centrifugation at 8000 rpm. The supernatant was collected and dialyzed for two days using a dialysis bag (molecular weight cutoff 500 Da) to remove the residual unreacted small molecules; the light brown g-CNQDs solution finally obtained showed strong blue fluorescence under ultraviolet light; In the control experiment, the EDTA content was adjusted so that the molar ratio of melamine and EDTA was between 6:1, 3:1, 2:1, 3:2, and 6:5, and these mixtures were calcined at 350°C for 1 h under the same conditions; in addition, the calcination temperature was changed from 200°C to 400°C to obtain different g-CNQDs fluorescence and chemiluminescence properties for analysis.

[0012] Further, in step S12, the quantum yield of g-CNQDs is determined by: determining the fluorescence quantum yield of g-CNQDs according to the reported literature; detecting the optical density of the g-CNQDs solution by UV-visible spectrophotometer, and using 0.1 mol / L quinine sulfate (quantum yield at 360 nm is 0.54) as a reference standard; using a standard reference sample with a fixed fluorescence quantum yield to calculate the absolute value of the sample, the formula is as follows: Where φ is the quantum yield, A is the optical density, I is the measured fluorescence intensity, and η is the refractive index; in order to minimize the reabsorption effect, the absorption at the excitation wavelength of 360 nm should be kept below 0.1.

[0013] Further, in step S13, the specific operation process is as follows: add 100 μL of g-CNQDs solution to a 2 mL quartz colorimetric cell, quickly add 100 μL (5 μmol / L) K3[Fe(CN)6] in 0.1 mol / L PBS buffer solution from the upper end of the BPCL detector using a micro syringe; flow injection chemiluminescence system such as Figure 3 The figure shows two flow paths, both with a flow rate of 70 rpm / min -1 Water is used as the carrier of g-CNQDs. g-CNQDs are injected through a six-way valve and mixed with the g-CNQDs-K3[Fe(CN)6] solution in another channel in a quartz coil above the photomultiplier tube to record the generated chemiluminescence signal. When detecting dopamine, different concentrations of dopamine are used instead of water as the carrier of g-CNQDs.

[0014] Furthermore, in step S14, the chemiluminescence spectrum of g-CNQDs-K3[Fe(CN)6] was measured under the condition that the xenon lamp of the fluorescence spectrometer was turned off, and the maximum emission was located at 550nm, indicating that the chemiluminescence position of g-CNQDs-K3[Fe(CN)6] was located at 550nm.

[0015] Furthermore, in step S21, the experimental reagents include a conductivity of 18.2 MΩcm -1 Deionized water, melamine, disodium ethylenediaminetetraacetate (EDTA), Ce(SO4)2 and Na2SO3 are used, and the experimental equipment is the same as that in step S11.

[0016] Further, in step S23, the specific operation process is: add 100 μL g-CNQDs solution and 100 μL 1 mMSO3 into a 2 mL quartz colorimetric cell. 2-Mix the solution and quickly add 100 μL (1 mmol / L) Ce in 0.1 mol / L H2SO4 buffer solution from the top of the BPCL detector with a micro-syringe; the chemiluminescence image and intensity are obtained under the condition of negative high voltage -800V of the photomultiplier tube with an integration time of 0.1 s; based on the above static chemiluminescence phenomenon, a flow injection chemiluminescence system is created. The flow injection chemiluminescence system includes three flow paths, and the flow rate is 12 rpm min -1 , water as SO3 2- The current carrier, SO3 2- The solution was injected through a six-way valve, and the water carrier was mixed with the other two Ce(IV) and g-CNQDs solutions in the quartz coil above the photomultiplier tube, and the generated chemiluminescence signal was recorded. When detecting iodine ions, different concentrations of iodine ions were used instead of water as the carrier of g-CNQDs. The peak value of the luminescence signal was recorded as the relative chemiluminescence intensity.

[0017] Furthermore, in step S24, the regression equation of the linear relationship is (lgI0-lgI)=0.033[I - ](μmol / L)+0.063, detection limit 5.8×10 -8 mol / L.

[0018] The present invention provides a chemiluminescence analysis method based on carbon nitride quantum dots, which has the following beneficial effects: The present invention discusses the properties of carbon nitride and deeply analyzes the luminescence characteristics of carbon nitride, and conducts research on carbon nitride in the field of chemiluminescence and related mechanism exploration and analytical applications.

[0019] (1) Carbon nitride quantum dots (g-CNQDs) were synthesized by a one-step green low-temperature solid-phase pyrolysis of melamine and EDTA. The g-CNQDs prepared have the advantages of good water solubility and high fluorescence efficiency. When g-CNQDs coexist with K3[Fe(CN)6], they can quickly produce a strong chemiluminescence response. The g-CNQDs-K3[Fe(CN)6] chemiluminescence reaction mechanism was studied by in-depth research on UV-visible spectroscopy, chemiluminescence spectroscopy, fluorescence spectroscopy, electron paramagnetic resonance and infrared spectroscopy. K3[Fe(CN)6] injects holes into g-CNQDs, which can combine with the thermally excited electrons of g-CNQDs to produce chemiluminescence. Based on this chemiluminescence phenomenon, a g-CNQDs-K3[Fe(CN)6] chemiluminescence system was created, and a flow injection chemiluminescence method was established to detect dopamine in serum. The analysis results showed good selectivity and high sensitivity, which has potential application value for the analysis of actual biological samples.

[0020] (2) g-CNQDs can significantly enhance the 2-The chemiluminescence of the system is nearly 60 times higher. The enhancement mechanism is studied based on chemiluminescence, UV-visible, fluorescence, infrared, electron energy and paramagnetic resonance. The results show that Ce(IV) injects holes into g-CNQDs to generate g-CNQDs•+, Ce(IV) and SO3 2- The •HSO3 free radicals produced by the reaction can inject electrons into g-CNQDs to obtain g-CNQDs•-, and the g-CNQDs•+ and g-CNQDs•- radiatively recombine to produce enhanced chemiluminescence. On the other hand, Ce(IV)-SO3 2- The SO2* produced by the chemiluminescent reaction can transfer energy to g-CNQDs, further enhancing the chemiluminescence. In addition, the enhancement effect was studied by changing the fluorescence efficiency and surface state of g-CNQDs. The study showed that the fluorescence efficiency affects the chemiluminescence signal, confirming the occurrence of chemiluminescence resonance energy transfer. 2- --The new chemiluminescence resonance energy transfer system of g-CNQDs has successfully established an analytical method for detecting the content of iodide ions in urine. This research work is the first to use g-CNQDs as a receptor for chemiluminescence resonance energy transfer, further expanding the application of g-CNQDs in the field of chemiluminescence. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A schematic diagram of a synthesis method of carbon nitride quantum dots in a document of a chemiluminescence analysis method based on carbon nitride quantum dots of the present invention; Figure 2 A schematic diagram of the synthesis of g-CNQDs by low-temperature solid-phase pyrolysis of melamine and EDTA based on a chemiluminescence analysis method of carbon nitride quantum dots according to the present invention; Figure 3 A schematic diagram of a flow injection g-CNQDs-K3[Fe(CN)6] chemiluminescence system device for a chemiluminescence analysis method based on carbon nitride quantum dots of the present invention; Figure 4 The chemiluminescence spectrum of the chemiluminescence analysis method based on carbon nitride quantum dots of the present invention is measured when the xenon lamp of the fluorescence spectrometer is turned off; Figure 5 A chemiluminescence spectrum of a chemiluminescence analysis method based on carbon nitride quantum dots of the present invention is measured by flow injection using a BPCL filter; Figure 6 The present invention is a flow injection detection method based on the chemiluminescence analysis of carbon nitride quantum dots with a concentration of (3.0×10 -5 –3.0×10 -7 ) Schematic diagram of the chemiluminescent signal of mol / L iodine ions; Figure 7This is a schematic diagram of a standard curve for detecting iodide ions in a chemiluminescence analysis method based on carbon nitride quantum dots of the present invention. DETAILED DESCRIPTION

[0022] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0023] like Figure 1-Figure 7 As shown, a chemiluminescence analysis method based on carbon nitride quantum dots comprises the following steps: S1. Green solid-phase method for preparing carbon nitride quantum dots for chemiluminescent detection of dopamine S11. Experimental reagents and instruments: Prepare all reagents and instruments required for the experiment, including a conductivity of 18.2 MΩcm -1 deionized water, melamine, disodium ethylenediaminetetraacetate, dopamine, 0.1 mol / L phosphate buffer solution, Na2HPO4 and NaH2PO4, etc., and the instruments include BPCL ultra-weak chemiluminescence analyzer, transmission electron microscope (TEM), atomic force microscope (AFM), XSAM800 (Kratos) XPS, etc.; In this example, the conductivity used in the experiment was 18.2 MΩcm -1 Deionized water was obtained from a water purification system (ULUPURE, Chengdu, China). Melamine (K3[Fe(CN)6]) and disodium ethylenediaminetetraacetate (EDTA) were purchased from Chengdu Reagent Co., Ltd., China. Dopamine was purchased from Adamas Reagent Co., Ltd. (Shanghai, China). All other reagents used in the experimental work were at least analytical grade (a grade of purity for chemical reagents) and were obtained from Changzheng Chemical Reagent Co., Ltd. (Chengdu, China). 0.1 mol / L phosphate buffer solution (PBS) was prepared by adjusting different volumes of Na2HPO4 and NaH2PO4 to the required pH values. Higher pH values ​​of 9–13 were adjusted by adding NaOH solution.

[0024] In addition, static chemiluminescence experiments were detected and recorded using a BPCL ultra-weak chemiluminescence analyzer (Institute of Biophysics, Chinese Academy of Sciences, Beijing, China), and the chemiluminescence peak height was used as the quantification of the chemiluminescence signal. Matching filters of different wavelengths (420, 460, 490, 535, 555, 575, 610, 640 nm) were placed between the flow cell and the photomultiplier tube to measure the chemiluminescence spectrum. Flow injection analysis was performed by using a peristaltic pump (Molel BT100-2, Baoding, China) to load the solution into the quartz coil located above the photomultiplier tube and quickly discharge it, thereby achieving batch analysis.

[0025] Transmission electron microscopy (TEM) is to drop the sample aqueous solution on the copper mesh carbon film, dry it under infrared light, and then place it on a Tecnai G2 F20 S-TWIN (FEI) field emission transmission electron microscope at an operating voltage of 200KV to characterize the material. Atomic force microscopy (AFM) (Agilent 5500AFM) is to drop the sample aqueous solution on the surface of a new mica sheet, vacuum dry it at 60°C, and scan and measure the sample thickness on the AFM using a cantilever probe tapping mode. The X-ray powder diffraction (XRD) of the sample is characterized by an X'PerPro (Philips) X-ray diffractometer, and the test conditions are: Cu target Ka ray (λ=1.54178Å), tube voltage 40KV, tube current 35Ma, scanning speed 0.01 o / s. X-ray photoelectron spectroscopy (XPS) characterization was performed using an XSAM800 (Kratos) XPS test photoelectron spectroscopy, and the test conditions were: Al target Ka ray (1486.6eV), the standard curve of binding energy was based on C1S at 282.8eV, power 150W, operating voltage 15KV, and analysis chamber vacuum 10-9torr. Fourier transform infrared spectroscopy (FTIR) testing was performed on a NicoletIS10 (Thermo) FTIR using the KBr pellet method, scanning in the range of 4000-400cm-1. Particle size and surface charge were analyzed and characterized using a laser particle size analyzer ZS (Malvern). Ultraviolet-visible spectroscopy (UV-Vis) and fluorescence spectroscopy (FL) were analyzed and tested using a U-2910 (Hitachi) UV-visible spectrophotometer and a F-7000 (Hitachi) fluorescence photometer, respectively.

[0026] In this example, human serum samples were obtained from three healthy adult volunteers. Protein was removed by centrifugation at 5000 rpm, and the supernatant (serum) was collected and placed in a refrigerator at 4°C for later use. The samples were diluted 100 times with ultrapure water for analysis.

[0027] S12, preparation of g-CNQDs: High fluorescence efficiency g-CNQDs were prepared by thermal decomposition of melamine and EDTA. Figure 1 As shown, 0.126 g (1 mmol) of melamine and 0.248 g (0.67 mmol) of EDTA were mixed and ground into a uniform powder, and the obtained mixed powder was placed in an alumina crucible and calcined in a muffle furnace at 350° C. for 1 hour.

[0028] After cooling to room temperature, 30 mL of ultrapure water was added to obtain a brown solution. The larger particles of byproducts were removed by centrifugation at 8000 rpm. The supernatant was collected and dialyzed for two days using a dialysis bag (molecular weight cutoff 500 Da) to remove the remaining unreacted small molecules. The resulting light brown g-CNQDs solution showed strong blue fluorescence under ultraviolet light. Figure 2 ; In the control experiment, the EDTA content was adjusted so that the molar ratio of melamine to EDTA was between 6:1, 3:1, 2:1, 3:2, and 6:5, and these mixtures were calcined at 350°C for 1h under the same conditions. In addition, the calcination temperature was changed from 200°C to 400°C to obtain different g-CNQDs. The fluorescence and chemiluminescence properties were analyzed.

[0029] Determination of quantum yield of g-CNQDs: The fluorescence quantum yield of g-CNQDs was determined according to the reported literature. The optical density of the g-CNQDs solution was detected by UV-visible spectrophotometer, and 0.1 mol / L quinine sulfate (quantum yield at 360 nm is 0.54) was used as the reference standard. The absolute value of the sample was calculated using a standard reference sample with a fixed fluorescence quantum yield, and the formula is as follows: Where φ is the quantum yield, A is the optical density, I is the measured fluorescence intensity, and η is the refractive index. In order to minimize the reabsorption effect, the absorption at the excitation wavelength of 360 nm should be kept below 0.1; S13, g-CNQDs-K3[Fe(CN)6] chemiluminescence: The chemiluminescence kinetic curve of g-CNQDs-K3[Fe(CN)6] was obtained by static injection chemiluminescence. The chemiluminescence image and intensity were obtained under the condition of negative high voltage -880V of photomultiplier tube with integration time 0.1s. The specific operation process is as follows: add 100μL g-CNQDs solution to 2mL quartz colorimetric cell, and quickly add 100μL (5μmol / L) K3[Fe(CN)6] in 0.1mol / L PBS buffer solution from the top of BPCL detector with a micro-syringe. Flow injection chemiluminescence system such as Figure 3 The figure shows two flow paths, both with a flow rate of 70 rpm / min -1 , water is used as the carrier of g-CNQDs, g-CNQDs are injected through a six-way valve, and the water-carried g-CNQDs-K3[Fe(CN)6] solution is mixed with the quartz coil above the photomultiplier tube, and the generated chemiluminescent signal is recorded. When detecting dopamine, different concentrations of dopamine are used instead of water as the carrier of g-CNQDs.

[0030] S14. Result analysis: K3[Fe(CN)6] is a commonly used chemiluminescent oxidant. In this study, it was found that when K3[Fe(CN)6] coexists with g-CNQDs, it will produce strong chemiluminescence, such as Figure 4-Figure 5 As shown, Figure 4 In the figure, the chemiluminescence kinetic curves of melamine (black line) and EDTA (blue line) after K3[Fe(CN)6] solution was added to g-CNQDs (red line) and heated. K3[Fe(CN)6] added to g-CNQDs quickly reached the highest point and gradually decreased, indicating that g-CNQDs and K3[Fe(CN)6] reacted chemically and gradually oxidized. However, the product heated with melamine or EDTA did not produce chemiluminescence with K3[Fe(CN)6], indicating that the chemiluminescence was indeed produced by g-CNQDs and K3[Fe(CN)6], rather than other products during the synthesis process. In addition, g-CNQDs did not produce chemiluminescence with K3[Fe(CN)6] under acidic or neutral conditions, indicating that g-CNQDs only produced strong chemiluminescence with K3[Fe(CN)6] under alkaline conditions. Based on this phenomenon, we created a new type of chemiluminescent system, which is more selective than the reported CDs and K3[Fe(CN)6] chemiluminescent system, avoids interference from other oxidants, and can produce stable and strong chemiluminescence at lower concentrations of K3[Fe(CN)6]. The chemiluminescence spectrum of g-CNQDs-K3[Fe(CN)6] was measured under the condition of xenon lamp off in the fluorescence spectrometer, and the maximum emission was at 550nm. The chemiluminescence spectrum measured using a series of chemiluminescence filters was similar to that of the fluorescence instrument, indicating that the chemiluminescence position of g-CNQDs-K3[Fe(CN)6] was at 550nm; S2. Carbon nitride quantum dot chemiluminescence resonance energy transfer for iodide ion detection: S21. Experimental reagents and instruments: Prepare all reagents and instruments required for the experiment, conductivity 18.2MΩcm -1 Deionized water was obtained from a water purification system (ULUPURE, Chengdu, China); melamine, disodium ethylenediaminetetraacetate (EDTA), Ce(SO4)2, and Na2SO3 were purchased from Chengdu Reagent Co., Ltd., China; other reagents used in the experimental work were at least analytical grade and were obtained from Changzheng Chemical Reagent Co., Ltd. (Chengdu, China); the experimental equipment was the same as step S11; S22. Chemical treatment of g-CNQDs: 0.1 mol / L NaBH4 was added dropwise to g-CNQDs and stirred for 2 h at room temperature, then placed in an ultrasonicator (100 W) for 10 h, and dialyzed in ultrapure water for 2 days to remove excess reducing agent to obtain reduced rg-CNQDs. Dialysis of g-CNQDs, Ce(IV) and SO3 2- The mixed solution after the reaction obtained oxidized og-CNQDs. The obtained rg-CNQDs and og-CNQDs solutions were freeze-dried, weighed, and dissolved in ultrapure water and stored in a refrigerator at 4°C; S23, Ce(IV)-SO3 2- -g-CNQDs chemiluminescence process: Ce(IV)-SO3 2- --The chemiluminescence kinetic curve of g-CNQDs was obtained by static injection chemiluminescence. The specific operation process was as follows: 100 μL g-CNQDs solution and 100 μL 1 mmol / L SO3 were added to a 2 mL quartz colorimetric cell. 2- Mix the solution and quickly add 100 μL (1 mmol / L) Ce in 0.1MH2SO4 buffer solution from the top of the BPCL detector with a micro syringe. The chemiluminescence image and intensity were obtained under the condition of negative high voltage -800V of the photomultiplier tube with an integration time of 0.1s. Based on the above static chemiluminescence phenomenon, a flow injection chemiluminescence system was created. The flow injection chemiluminescence system contains three flow paths, and the flow rate is 12 rpm min -1 , water as SO3 2- The current carrier, SO3 2- Injected through a six-way valve, the water-carried solution is mixed with the other two Ce(IV) and g-CNQDs solutions in the quartz coil above the photomultiplier tube, and the generated chemiluminescent signal is recorded. When detecting iodine ions, different concentrations of iodine ions are used to replace water as the carrier of g-CNQDs. The peak value of the luminescent signal is recorded as the relative chemiluminescent intensity.

[0031] In this example, human urine samples were obtained from healthy volunteers. The samples were centrifuged at 8000 rpm for 10 min, and the supernatant was collected and diluted 100 times for testing.

[0032] S24. Result analysis: Under the optimal experimental conditions, the analytical sensitivity of detecting different concentrations of iodide ions is as follows: Figure 6-Figure 7 As shown in the figure, the chemiluminescence signal and the iodide ion concentration are (3.0×10 -5 –3.0×10 -7 )mol / L has good linearity, and the linear regression equation is (lgI0-lgI)=0.033[I - ](μmol / L)+0.063, detection limit 5.8×10-8 mol / L.

[0033] The embodiments of the present invention are given for the purpose of illustration and description, and are not intended to be exhaustive or to limit the invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.

Claims

1. A chemiluminescence analysis method based on carbon nitride quantum dots, characterized in that: The following steps are involved: S1. Green solid phase method for preparing carbon nitride quantum dots for chemiluminescent detection of dopamine; S11. Experimental reagents and instruments: prepare all reagents and instruments required for the experiment; S12, preparation of g-CNQDs: g-CNQDs with high fluorescence efficiency were prepared by thermal decomposition of melamine and EDTA; S13, g-CNQDs-K3[Fe(CN)6] chemiluminescence: The kinetic curve of g-CNQDs-K3[Fe(CN)6] chemiluminescence was obtained by static injection chemiluminescence, and the chemiluminescence image and intensity were obtained under the condition of negative high voltage -880V of photomultiplier tube with integration time of 0.1s; S14. Result analysis: K3[Fe(CN)6] is a commonly used chemiluminescent oxidant. Studies have found that when K3[Fe(CN)6] coexists with g-CNQDs, it will produce strong chemiluminescence; S2. Carbon nitride quantum dot chemiluminescence resonance energy transfer for iodide ion detection: S21. Experimental reagents and instruments: prepare all reagents and instruments required for the experiment; S22. Chemical treatment of g-CNQDs: 0.1 mol / L NaBH4 was added dropwise to g-CNQDs and stirred for 2 h at room temperature, then placed in an ultrasonic instrument (100 W) for 10 h, and dialyzed in ultrapure water for 2 days to remove excess reducing agent to obtain reduced rg-CNQDs; dialyzed g-CNQDs, Ce(IV) and SO3 2- The mixed solution after the reaction obtained oxidized og-CNQDs; the obtained rg-CNQDs and og-CNQDs solutions were freeze-dried, weighed, and dissolved in ultrapure water in the same mass and stored in a refrigerator at 4°C; S23, Ce(IV)-SO3 2- -g-CNQDs chemiluminescence process: Ce(IV)-SO3 2- --The kinetic curve of g-CNQDs chemiluminescence was based on static injection chemiluminescence; S24. Result analysis: Under the optimal experimental conditions, the analytical sensitivity of different concentrations of iodine ions was detected. The chemiluminescence signal and iodine ion concentration were (3.0×10 -5 –3.0×10 -7 )mol / L has good linearity.

2. A chemiluminescence analysis method based on carbon nitride quantum dots according to claim 1, characterized in that: In step S11, the experimental reagents include a conductivity of 18.2 MΩcm -1 Deionized water, melamine, disodium EDTA, dopamine, 0.1 mol / L phosphate buffer solution, Na2HPO4 and NaH2PO4.

3. The chemiluminescence analysis method based on carbon nitride quantum dots according to claim 1, characterized in that: In the step S11, the experimental instruments include a BPCL ultra-weak chemiluminescence analyzer, a transmission electron microscope, an atomic force microscope, and an XSAM800 XPS; The transmission electron microscope is to drop the sample aqueous solution on the copper mesh carbon film, dry it under an infrared lamp to be tested, and then place it in a Tecnai G2 F20 S-TWIN field emission transmission electron microscope to characterize the material under the operating voltage of 200KV; The atomic force microscope is to drop the sample aqueous solution on the surface of a new mica sheet, dry it in vacuum at 60°C, and then use a cantilever probe tapping mode to scan and measure on the AFM to test the sample thickness.

4. The chemiluminescence analysis method based on carbon nitride quantum dots according to claim 1, characterized in that: In step S12, the specific preparation steps of g-CNQDs are as follows: 0.126 g of melamine and 0.248 g of EDTA were mixed and ground into a uniform powder, and the obtained mixed powder was placed in an alumina crucible and calcined in a muffle furnace at 350° C. for 1 hour; After cooling to room temperature, 30 mL of ultrapure water was added to obtain a brown solution, and the byproducts with larger particles were removed by centrifugation at 8000 rpm. The supernatant was collected and dialyzed for two days using a dialysis bag to remove the residual unreacted small molecules. The light brown g-CNQDs solution obtained finally showed strong blue fluorescence under ultraviolet light. In the control experiment, the EDTA content was adjusted so that the molar ratio of melamine and EDTA was between 6:1, 3:1, 2:1, 3:2, and 6:5, and these mixtures were calcined at 350°C for 1 h under the same conditions; in addition, the calcination temperature was changed from 200°C to 400°C to obtain different g-CNQDs fluorescence and chemiluminescence properties for analysis.

5. The chemiluminescence analysis method based on carbon nitride quantum dots according to claim 1, characterized in that: In step S12, the quantum yield of g-CNQDs is determined by measuring the fluorescence quantum yield of g-CNQDs according to the reported literature; the optical density of the g-CNQDs solution is detected by a UV-visible spectrophotometer, and 0.1 mol / L quinine sulfate is used as a reference standard; the absolute value of the sample is calculated using a standard reference sample with a fixed fluorescence quantum yield, and the formula is as follows: Where φ is the quantum yield, A is the optical density, I is the measured fluorescence intensity, and η is the refractive index.

6. The chemiluminescence analysis method based on carbon nitride quantum dots according to claim 1, characterized in that: In step S13, the specific operation process is as follows: add 100 μL of g-CNQDs solution to a 2 mL quartz colorimetric cell, and quickly add 100 μL (5 μmol / L) K3[Fe(CN)6] in 0.1 mol / L PBS buffer solution from the upper end of the BPCL detector using a micro syringe; the flow injection chemiluminescence system includes two flow paths, and the flow rate is 70 rpm min -1 Water is used as the carrier of g-CNQDs. g-CNQDs are injected through a six-way valve and mixed with the g-CNQDs-K3[Fe(CN)6] solution in another channel in a quartz coil above the photomultiplier tube to record the generated chemiluminescent signal. When detecting dopamine, different concentrations of dopamine are used instead of water as the carrier of g-CNQDs.

7. The chemiluminescence analysis method based on carbon nitride quantum dots according to claim 1, characterized in that: In step S14, the chemiluminescence spectrum of g-CNQDs-K3[Fe(CN)6] is measured under the condition that the xenon lamp of the fluorescence spectrometer is turned off, and the maximum emission is located at 550nm, indicating that the chemiluminescence position of g-CNQDs-K3[Fe(CN)6] is located at 550nm.

8. The chemiluminescence analysis method based on carbon nitride quantum dots according to claim 1, characterized in that: In step S21, the experimental reagents include a conductivity of 18.2 MΩcm -1 Deionized water, melamine, disodium ethylenediaminetetraacetate (EDTA), Ce(SO4)2 and Na2SO3 are used, and the experimental equipment is the same as that in step S11.

9. The chemiluminescence analysis method based on carbon nitride quantum dots according to claim 1, characterized in that: In step S23, the specific operation process is as follows: add 100 μL of g-CNQDs solution and 100 μL of 1 mmol / L SO3 into a 2 mL quartz colorimetric cell. 2- Mix the solution and quickly add 100 μL (1 mmol / ) Ce in 0.1 mol / L H2SO4 buffer solution from the top of the BPCL detector with a micro-syringe; the chemiluminescence image and intensity are obtained under the condition of negative high voltage -800V of the photomultiplier tube with an integration time of 0.1 s; based on the above static chemiluminescence phenomenon, a flow injection chemiluminescence system is created. The flow injection chemiluminescence system includes three flow paths, and the flow rate is 12 rpm min -1 , water as SO3 2- The current carrier, SO3 2- The solution was injected through a six-way valve, and the water carrier was mixed with the other two Ce(IV) and g-CNQDs solutions in the quartz coil above the photomultiplier tube, and the generated chemiluminescence signal was recorded. When detecting iodine ions, different concentrations of iodine ions were used instead of water as the carrier of g-CNQDs. The peak value of the luminescence signal was recorded as the relative chemiluminescence intensity.

10. The chemiluminescence analysis method based on carbon nitride quantum dots according to claim 1, characterized in that: In step S24, the regression equation of the linear relationship is (lgI0-lgI)=0.033[I - ](μmol / L)+0.063, detection limit 5.8×10 -8 mol / L.